High-intensity versus low-intensity non-invasive ventilation in patients with stable hypercapnic COPD: a randomised crossover trial. Issue 4 (13th April 2010) - Dreher, Michael; Storre, Jan H; Schmoor, Claudia; Windisch, Wolfram
Abstract : Rationale: The conventional approach of low-intensity non-invasive positive pressure ventilation (NPPV) produces only minimal physiological and clinical benefits in patients with stable hypercapnic chronic obstructive pulmonary disease (COPD). Objectives: To determine whether the novel approach of high-intensity NPPV is superior to low-intensity NPPV in controlling nocturnal hypoventilation. Methods: A randomised controlled crossover trial comparing 6 weeks of high-intensity NPPV (using controlled ventilation with mean inspiratory pressures of 28.6±1.9 mbar) with low-intensity NPPV (using assisted ventilation with mean inspiratory pressures of 14.6±0.8 mbar) was performed in 17 patients with severe stable hypercapnic COPD. Results: Two patients refused low-intensity NPPV and two patients dropped out while on low-intensity NPPV. Thirteen patients (mean forced expiratory volume in 1 s (FEV1 ) 0.76±0.29 l) completed the trial. High-intensity NPPV produced higher pneumotachographically-measured expiratory volumes, with a mean treatment effect of 96 ml (95% CI 23 to 169) (p=0.015). This resulted in a mean treatment effect on nocturnal arterial carbon dioxide tension (Paco2 ) of −9.2 mm Hg (95% CI −13.7 to −4.6) (p=0.001) in favour of high-intensity NPPV. Daily use of NPPV was increased in high-intensity NPPV compared with low-intensity NPPV, with a mean difference of 3.6 h/day (95% CI 0.6 to 6.7) (p=0.024). In addition, compared with baseline, only high-intensity NPPV resulted in significant improvements in exercise-related dyspnoea, daytime Paco2, FEV1, vital capacity and the Severe Respiratory Insufficiency Questionnaire Summary Score. Conclusions: High-intensity NPPV is better tolerated by patients with severe chronic hypercapnic COPD and has been shown to be superior to the conventional and widely-used form of low-intensity NPPV in controlling nocturnal hypoventilation. High-intensity NPPV therefore offers a new promising therapeutic option for these patients.